2022
DOI: 10.3389/fpsyg.2022.867122
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Learning Engagement in the Context of Online Learning During the COVID-19 Pandemic

Abstract: The main aim of the present research is to analyze the predictive value of individual characteristics such as online self-efficacy, adaptability to uncertainty, and sources of stress during online learning on learning engagement. We also aimed to highlight if these relationships could be mediated by the online self-regulated learning strategies, during the COVID-19 pandemic. The participants were 529 university students and the design was cross-sectional. The results showed significant associations of the sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 67 publications
3
12
0
Order By: Relevance
“…A study on learning engagement in online mathematics courses found that learning motivation can promote students’ learning engagement through self-management and control of effort and attention, and adjustment of learning strategies ( Kim et al, 2015 ). Similarly, an empirical study has also found that self-regulated learning has a significant impact on learning engagement ( Stan et al, 2022 ). Based on the above literature, we propose our first hypothesis: There is a significantly positive correlation between self-regulated learning and online mathematics learning engagement among junior high school students.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…A study on learning engagement in online mathematics courses found that learning motivation can promote students’ learning engagement through self-management and control of effort and attention, and adjustment of learning strategies ( Kim et al, 2015 ). Similarly, an empirical study has also found that self-regulated learning has a significant impact on learning engagement ( Stan et al, 2022 ). Based on the above literature, we propose our first hypothesis: There is a significantly positive correlation between self-regulated learning and online mathematics learning engagement among junior high school students.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Recently, researchers have demonstrated that many learner characteristics and external factors can effectively predict student online learning engagement. The factors included the quality of teacher-student interaction ( Lu and Churchill, 2014 ), peer relationships ( Shao and Kang, 2022 ), self-handicapping ( Holliman et al, 2018 ), and self-regulation ( Stan et al, 2022 ), among others. Among the preconditions that influence online mathematics learning engagement, self-regulating learning (SRL) is especially important.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, nonpregnant users with larger families for whom they provide care, tend to be avid web-based health information consumers [9]. In more recent articles, sociodemographic characteristics strongly associated with digital health information seeking included socioeconomic status, age, ethnicity, and college-level education [10,11]. Further, another recent analysis found that self-efficacy had positive effects on the extent of learner engagement with educational resources [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies on student engagement in online settings have limitations and merit further research. The majority of literature works are cross-sectional studies, focusing exclusively on the beginning or end of the learning sessions [11,12,13]. Data collected at a fixed point in time do not describe the changing nature of learners' engagement in learning.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%